(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Conventional architectures based on a central servers are not suitable and cannot scale well in a distributed and high dynamic computing enviroment. Futuristic ubiquitous landscape requires the development of robust, reliable and flexible distributed information systems capable of large scaling and supporting the large amount of simultaneous user requests. In this paper, we propose an innovative information system based on intelligent agents, which is capable of optimizing the search task and managing the services within a coalition of intelligent agents. Users will request a set of information services provided by information providers distributed among a Big Data Network (BDN). The system is divided into two subsystems. The first subsystem is responsible for the search optimization task using an evolutionary algorithm. It generates optimized Workpans for mobile agents that collect needed data from the BDN. The scond subsystem is composed of coalitions of peer agents whitch are endowed with the ability of role switching. A peer agent is by default a passive agent (client), once it receives a given service it can switch its role to become an active agent (service provider) for a given period of time. We provide in the end of this paper simulations supporting our claims about role switching performances and statistical results about the coalition of agents before and after role switching.